A Property of K_2n+1 as the Sum of n Spanning Cycles: Hatairat Yingtaweesittikul, Vites Longani - Team, Support (Thai Journal of Mathematics, 2022)
It is known that K_2n+1 is the sum of n spanning cycles. In this paper we show that when 2n+1 is prime number we can have additional property that all lines of the first cycle have distances 1, all lines of the second cycle have distances 2, …., and all lines of the n-th cycle have distances n. Also, when 2n+1 is not prime number, this property is not possible.